The effect of creative drama on the creative self-efficacy of pre-service teachers - Bircan Eyüp (Journal of Pedagogical Research, 2023)
The present study aims to examine the effect of creative drama practices on the creative self-efficacy of pre-service Turkish language teachers and their opinions on the practices. The study was designed based on the mixed explanatory sequential design. The study group consisted of 22 (13 female, 9 male) pre-service Turkish language teachers attending the Department of Turkish Language Teaching at the faculty of education in a state university. In the quantitative section of the study, a one-group pretest-posttest experimental design was employed. Phenomenology was utilized in the qualitative section. The Creative Self-Efficacy Scale was used to collect quantitative data and a semi-structured focus group interview form was used to collect qualitative data. The activities were carried out in 90-minute sessions once a week for a total of 21 hours. The pretest and posttest results showed that the creative drama activities carried out in the study group were effective in increasing the creative self-efficacy of the pre-service Turkish teachers. According to the results obtained from the focus group interviews, it was determined that the pre-service teachers expressed positive views regarding creative drama practices in terms of their creative self-efficacy. As a result of the study, it was concluded that creative drama practices contributed positively to the creative self-efficacy of the pre-service Turkish teachers.